MINAT PENGGUNAAN CASHLESS PAYMENT SISTEM DOMPET DIGITAL PADA MAHASISWA DI PAPUA BARAT - Rahman, Mohammad Arief; Warokka, Ari; Priyati, Rini Yayuk (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research examines the factors influencing the intention to use digital payment applications (cashless payments) among students in West Papua. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, this research analyzes the influence of self-efficacy, perceived risk, perceived usefulness, perceived ease of use, brand loyalty, and user attitudes on intentions to use cashless payment applications, as well as mediation potential user attitudes towards the influence of perceived usefulness and perceived ease of use. This research uses a questionnaire to apply a quantitative study of 342 West Papuan students. The analysis includes validity, reliability, and structural models. The research results show that self-efficacy and perceived risk do not significantly affect intention to use. In contrast, perceived usefulness, ease of use, brand loyalty, and user attitude have a significant effect. Besides that, user attitude can mediate the influence of perceived usefulness and ease of use on intention to use.